(untitled) (Bioresearch Communications, 2024)
The problem of the present study was to investigate whether there is any effect of verbal reinforcement and verbal punishment on performance. The experiment was conducted on some young adult participants. The objective of the present study was to assess whether usual verbal reinforcement influenced performance more than the verbal punishment. It was hypothesized that positive verbal reinforcement would have a significantly greater impact on respondents’ performance than positive verbal punishment. We adopted a between group design where 20 undergraduate students were randomly assigned to two conditions, namely positive verbal reinforcement and positive verbal punishment. We provided the interventions through a small, structured interview where the positive verbal reinforcement group were handled warmly but the other group were not. Then we asked them to complete two specially designed monotonous tasks and measured their duration of engagement in the tasks as a measure of performance. The mean durations of engagement for the positive verbal reinforcement and positive verbal punishment groups were 1555.90 seconds and 675.90 seconds, respectively, which differed significantly at the .006 level with a t-value of 3.11 (df=18). And thus, we concluded that positive verbal reinforcement is more powerful to enhance performance than the positive verbal punishment. Bioresearch Commu. 10(2): 1609-1611, 2024 (July)